Antimicrobial effects of XF drugs against Candida albicans and its biofilms - Board-Davies, E. L.; Rhys-Williams, W.; Hynes, D.; Love, W. G.; Williams, D. W. (Frontiers in Fungal Biology, 2023)
Compared with antibiotics for treating bacterial infections, there are a limited number of antifungal agents. This occurs from several factors, including the difficulties of identifying suitable antifungals that target the fungal cell without damaging host cells, and the reduced recognition of fungal infections compared to those caused by bacteria. The problem of treating fungal infections is exacerbated by an increasing incidence of antifungal resistance amongst human fungal pathogens. Three XF-Drugs (XF-73, XF-70 and DPD-207) have previously displayed innate bactericidal effects and a low propensity for microbial resistance, with XF-73 and XF-70 having a second, light activated (photodynamic therapy; PDT) mechanism of action. In an effort to expand the repertoire of antifungal agents, this research assessed the in vitro activity of XF-Drugs via both mechanisms of action against six strains of the fungal pathogen Candida albicans in planktonic and biofilm cultures. In addition, research examined the effects of XF-Drug treatment of biofilms of C. albicans in a reconstituted human oral epithelium model. All C. albicans strains tested were susceptible to XF-73 and XF-70, with minimum inhibitory concentrations (MICs) between 0.25-2 µg/mL, DPD-207 was less potent with MICs 4-16 µg/mL and light activation did not enhance the MICs. Complete biofilm eradication was not reported at the tested XF-Drug concentrations. However, live and dead staining of C. albicans cells in biofilms after XF-Drug treatment demonstrated that XF-73 and XF-70 were active against most Candida biofilms tested from 64 µg/mL, again light activation did not enhance anti-biofilm activity. Candida biofilms were more resistant to DPD-207, with fungicidal effects occurring from 256 µg/mL. XF-73 and XF-70 reduced penetration of C. albicans biofilm into a reconstituted human oral epithelium (RHOE) and resulted in lower damage (as determined by reduced lactate dehydrogenase release) compared to untreated biofilms. Overall, the results highlight the potential of XF-Drugs as new drugs for the management of topical infections caused by C. albicans. Further studies are warranted with regards to the development of XF-Drugs as antifungals, and particularly for XF-73 and XF-70.